Explaining the gender gaps in mathematics achievement and attitudes: the role of societal gender equality - Gevrek, Z. Eylem (2020)
The gender stratification hypothesis maintains that higher levels of societal gender equity predict smaller gender gaps in mathematics achievement and attitudes. Using data from the Program for International Student Assessment (PISA) across 56 countries, this study aims to provide a thorough empirical test of the gender stratification hypothesis. We employ a novel two-stage empirical strategy to investigate the link between societal gender equities and gender differences in mathematics achievement and attitudes. In the first stage, we use a semiparametric Oaxaca-Blinder (OB) method to decompose the gender gaps in each country into a part that is explained by gender differences in observable characteristics and a part that remains unexplained. In the second stage, we examine the relationships between the unexplained parts of the gender gaps and country-specific gender equity measures. The results highlight the importance of gender equity in the labor market in explaining cross-country variation in the gender math gap. We find that lower gender wage gap is significantly associated with a smaller unexplained part of the gender math gap favoring boys. In terms of the gender gaps in math attitudes, the results yield mixed support for the gender stratification hypothesis.